Physiological, Behavioral, and Life-History Adaptations to Environmental Fluctuations in the Edible Dormouse - Ruf, Thomas; Bieber, Claudia (Frontiers in Physiology, 2020)
The edible dormouse (Glis glis, formerly Myoxus glis) is a small arboreal mammal inhabiting deciduous forests in Europe. This rodent shows behavioral and physiological adaptations to three types of environmental fluctuations: (i) predictable seasonal variation in climate and food resources (ii) unpredictable year-to-year fluctuation in seed-production by trees and (iii) day-to-day variation in ambient temperature and precipitation. They cope with seasonally fluctuating conditions by seasonal fattening and hibernation. Dormice have adjusted to tree-mast fluctuations, i.e., pulsed resources, by sensing future seed availability in spring, and restricting reproduction to years with at least some seed production by beech and oak trees, which are a crucial food-resource for fast-growing juveniles in fall. Finally, dormice respond to short-term drops in ambient temperature by increased use of daily torpor as well as by huddling in groups of up to 24 conspecifics. These responses to environmental fluctuations strongly interact with each other: Dormice are much more prone to using daily torpor and huddling in non-reproductive years, because active gonads can counteract torpor and energy requirements for reproduction may prevent the sharing of food resources associated with huddling. Accordingly, foraging activity in fall is much more intense in reproductive mast years. Also, depending on their energy reserves, dormice may retreat to underground burrows in the summers of non-reproductive years, causing an extension of the hibernation season to up to 11.4 months. In addition to these interactions, responses to environmental fluctuations are modulated by the progression of life-history stages. With increasing age and diminishing chances of future reproduction, females reproduce with increasing frequency even under suboptimal environmental conditions. Simultaneously, older dormice shorten the hibernation season and phase-advance the emergence from hibernation in spring, apparently to occupy good breeding territories early, despite increased predation risk above ground. All of the above adaptions, i.e., huddling, torpor, hibernation, and reproduction skipping do not merely optimize energy-budgets but also help to balance individual predation risk against reproductive success, which adds another layer of complexity to the ability to make flexible adjustments in this species.